Unlocking retirement choices: factors shaping savings scheme selections in sabah's statutory bodies and local authorities - Zaiton Osman; Aidarina Jakaria (Penerbit Universiti Malaysia Sabah, 2024)
This study was carried out to seek deeper understanding of why statutory bodies and local authority employees are more attracted to choose the Government pension over the EPF contribution as a retirement scheme. Specifically, it was conducted to examine the knowledge and understanding of retirement schemes available to them and to determine factors affecting employee’s evaluation of the Government pension and the EPF retirement schemes. The Theory of Planned Behaviour (Ajzen 2000) was used as the research framework, and quantitative method was employed as the approach to research. There were three major findings from this research. Firstly, employees were aware, understand the choice and can differentiate between the two schemes. However, their awareness level was rather low for them to make informed choices. Secondly, social factors formed the basis in making the choice meanwhile psychological factors established the need to make the choice. However, economic factors were the determining factor in making the decision to choose a scheme. Income level, age, and gender were significantly moderating variables influencing the decision to choose a pension scheme.